Association between common cardiovascular drugs and depression. Issue 22 (20th November 2021) - Tao, Shu-Hui; Ren, Xue-Qun; Zhang, Li-Jun; Liu, Mei-Yan
Abstract: Objective: Cardiovascular diseases are associated with an increased risk of depression, but it remains unclear whether treatment with cardiovascular agents decreases or increases this risk. The effects of drugs on individual usage are also often unknown. This review aimed to examine the correlation between depression and common cardiovascular drugs, develop more potent interventions for depression in cardiovascular patients, and further research on the bio-behavioural mechanisms linking cardiovascular drugs to depression. Data sources: The data in this review were obtained from articles included in PubMed, EMBASE, and Web of Science. Study selection: Clinical trials, observational studies, review literature, and guidelines about depression and cardiovascular drugs were selected for the article. Results: We systematically investigated whether the seven most used cardiovascular drugs were associated with altered risk of incident depression in this literature review. Statins have been proven to have antidepressant effects. Some studies believe angiotensin-converting enzyme inhibitors (ACEIs)/angiotensin receptor blocker (ARB) can exert an antidepressant influence by acting on the renin-angiotensin system, but further clinical trials are needed to confirm this. Beta-blockers have previously been associated with depression, but the current study found no significant association between beta blockers and the risk of depression. Aspirin may have antidepressant effects by suppressing the immune response, but its role as an antidepressant remains controversial. calcium channel blockers (CCBs) can regulate nerve signal transduction by adjusting calcium channels, but whether this effect is beneficial or harmful to depression remains unclear. Finally, some cases have reported that nitrates and diuretics are associated with depression, but the current clinical evidence is insufficient. Conclusions: Statins have been proven to have antidepressant effect, and the antidepressant effects of ACEIs/ARB and aspirin are still controversial. CCBs are associated with depression, but it is unclear whether it is beneficial or harmful. No association has been found with β-blockers, diuretics, and nitrates.